Evaluation of sorbitan monolaurate concentration on carrageenan gel properties - Nur Aishah Balqis, Mohd Hilmy; Nur Anis Alisya, Kamarol Zani; Nur Amalina, Ramli; Fatmawati, Adam; Muhamad Hadi, Sulaiman (School of Chemical Engineering, College of Engineering, Universiti Teknologi MARA, 2022)
Air fresheners are chemical products that have been used in the field of environmental sanitation for decades. The brands, materials and types of fragrance air fresheners have been developed to reduce the depression level amongst people. This study used seaweed from carrageenan to explore renewable resources from Malaysia as biopolymer. It is proven that the mild depression or stress can be released with help of aromatherapy substances, and one is aromatherapy scented gel. The objectives of this study were to formulate and characterize the scented gel from carrageenan and the stability of the scented gel. The gel was produced by mixing sorbitan monolaurate (surfactant) and carrageenan in water. Then, polyethylene glycol (PEG), alginic acid and essential oil were added into the mixture. The solution viscosity and shear stress for rheology properties were measured. The highest viscosity was the sample without sorbitan monolaurate which is 979.37 mPa·s while the highest shear stress was 0.50% (v/v) sorbitan monolaurate with 296.42 Pa. Moreover, for weight variation analysis, sample with 0.5% (v/v) sorbitan monolaurate showed the lowest residual loss which is 11.8% compared samples with higher concentration of sorbitan monolaurate. Bloom test demonstrated samples with 1.50, 2.00, and 2.50% (v/v) have high bloom when the gel strength increased at higher concentration of sorbitan monolaurate. Sorbitan monolaurate of 0.5% (v/v) of is a stable gel with high mass of residue. In conclusion, gel air freshener could be produced from carrageenan to replace other gelling material such as gelatin, xanthan gum and guar gum.